Gut microbial community supplementation and reduction modulates African armyworm susceptibility to a baculovirus. Issue 1 (6th December 2022) - Donkersley, Philip; Rice, Annabel; Graham, Robert I; Wilson, Kenneth
Abstract: Gut microbiota stimulates the immune system and inhibits pathogens, and thus, it is critical for disease prevention. Probiotics represent an effective alternative to antibiotics used for the therapy and prevention of bacterial diseases. Probiotic bacteria are commonly used in vertebrates, although their use in invertebrates is still rare. We manipulated the gut microbiome of the African Armyworm ( Spodoptera exempta Walker) using antibiotics and field-collected frass, in an attempt to understand the interactions of the gut microbiome with the nucleopolyhedrovirus, SpexNPV. We found that S. exempta individuals with supplemented gut microbiome were significantly more resistant to SpexNPV, relative to those with a typical laboratory gut microbiome. Illumina MiSeq sequencing revealed the bacterial phyla in the S. exempta gut belonged to 28 different classes. Individuals with an increased abundance of Lactobacillales had a higher probability of surviving viral infection. In contrast, there was an increased abundance of Enterobacteriales and Pseudomonadales in individuals dying from viral infection, corresponding with decreased abundance of these two Orders in surviving caterpillars, suggesting a potential role for them in modulating the interaction between the host and its pathogen. These results have important implications for laboratory studies testing biopesticides. Abstract : Our study examines how lab strains of a widespread insect pest species (the African Armyworm) have a distinct gut microbiome and the role that gut microbes play in affecting resistance to nucleopolyhedrovirus, SpexNPV. Through a combination of antiobiotic control and field-collected frass innoculations, we demonstrate that inoculation of the field microbiome of this pest species into lab strains increases resistance to the virus, and that this is subsequently reversed when treated with a broad spectrum antibiotic.